THE EXPLORATION OF ETHNOMATHEMATICS IN PANDEGLANG TRADITIONAL FOOD - Meika, Ika; Nadila, Dila; Yunitasari, Ika (UIN Imam Bonjol Padang, 2024)
Ethnomathematics is a mathematical concept that combines cultural elements such as regional songs, regional dances, traditional games, traditional food, and other cultural heritage into mathematics education. The presence of ethnomathematics can bridge education and culture. Pandeglang is a district in Banten province, which has a variety of cultures, one of which is traditional food. Traditional Pandeglang food contains elements of mathematics if you look at its form. The aim of this research is to explore ethnomathematics in traditional Pandeglang food and make traditional food a source of learning mathematics. As for traditional Pandeglang food, the objects of research are white apem, opak, block cake and pasung cake. This research uses qualitative methods with an emographic approach. The techniques used in data collection were carried out through observation, interviews and documentation. The results obtained from this research show that there are mathematical concepts, namely flat geometric shapes and spatial shapes in traditional Pandeglang food. Thus, traditional Pandeglang food can be used as a source of learning mathematics starting from phase A to phase D, so that learning mathematics becomes more meaningful. for students, because learning resources are often encountered in everyday life.